2010
DOI: 10.1021/ac100177j
|View full text |Cite
|
Sign up to set email alerts
|

Propagating Surface Plasmon Resonance on Microhole Arrays

Abstract: Metallic thin films patterned with micrometer size triangle or hole arrays present plasmonic properties when excited in the Kretschmann configuration, that are improved in comparison to conventional thin film surface plasmon resonance (SPR). These optical properties can be tuned by varying the physical aspects of the microplasmonic structures. Triangles and microhole arrays were prepared with modified nanosphere lithography (NSL) using latex spheres of 0.65, 0.82, 1.0, 1.5, or 3.2 microm in diameter. This allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 39 publications
0
59
0
Order By: Relevance
“…Furthermore, bimetallic nanohole arrays composed of a Ag underlayer covered with Au exhibited an improved sensitivity, stability, and FWHM compared with nanohole arrays of pure metal. This field considerably accelerated in the last years, and the sensitivities of various shapes were examined [180]. Lee et al [181] found that the sensitivities of nanohole arrays, concentric circles, and nanoslits are 560 nm/RIU, 623 nm/RIU, and 650 nm/RIU, respectively.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…Furthermore, bimetallic nanohole arrays composed of a Ag underlayer covered with Au exhibited an improved sensitivity, stability, and FWHM compared with nanohole arrays of pure metal. This field considerably accelerated in the last years, and the sensitivities of various shapes were examined [180]. Lee et al [181] found that the sensitivities of nanohole arrays, concentric circles, and nanoslits are 560 nm/RIU, 623 nm/RIU, and 650 nm/RIU, respectively.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…110,108 This tunability for a particular application of interest allows for dramatic increases in SPR sensitivity. 107,[118][119][120] Although the tunability of such nanoarrays in gold is limited to the NIR and longer wavelength region of the visible (i.e., ∼500 nm or greater), a variation of these nanoslit and nanohole arrays, known as nanotriangle arrays [see Fig. 8(f)], 107 has demonstrated the ability to further expand the range of LSPR wavelengths achievable simply by altering the structure.…”
Section: Recent Advances In Surface Plasmonmentioning
confidence: 99%
“…107,[118][119][120] Although the tunability of such nanoarrays in gold is limited to the NIR and longer wavelength region of the visible (i.e., ∼500 nm or greater), a variation of these nanoslit and nanohole arrays, known as nanotriangle arrays [see Fig. 8(f)], 107 has demonstrated the ability to further expand the range of LSPR wavelengths achievable simply by altering the structure. This demonstrates the vast potential of various nanostructures for enhanced SPR sensing.…”
Section: Recent Advances In Surface Plasmonmentioning
confidence: 99%
“…3D) are structures consisting of hexagonally patterned holes embedded in an Au film with a hole diameter of the order of 500 nm to 2 μm and periodicity of the order of a few microns [23]. Microhole arrays share properties of gratings, as they can also be viewed as thin stripes of Au repeating at a rotational angle of 60°.…”
Section: Enhancing Sensitivity With Nanostructured Substratesmentioning
confidence: 99%
“…Refractive index sensitivity was enhanced by at least a factor of 2 in comparison with thin Au film with microhole arrays. Detection of IgG was also enhanced by approximately the same factor [23]. The excitation of the SP on microhole arrays with a Dove prism SPR [24] led to a refractive index resolution of 1.5×10 −6 RIU, equivalent to thin film SPR sensors; the comparison was performed on the same instrumentation [23].…”
Section: Enhancing Sensitivity With Nanostructured Substratesmentioning
confidence: 99%